2013
DOI: 10.21897/rmvz.195
|View full text |Cite
|
Sign up to set email alerts
|

Las proteínas del plasma seminal incrementan la viabilidad espermática post-descongelación del semen de toros Sanmartinero

Abstract: RESUMENObjetivo. El objetivo de este trabajo fue evaluar el efecto de la adición de proteínas del plasma seminal sobre el porcentaje de espermatozoides bovinos viables post-descongelación. Materiales y métodos. Los espermatozoides se congelaron usando dos medios (citrato-fructosa-yema y Bioxcell ® ) y la obtención de proteínas de plasma seminal de bajo peso molecular se realizó por medio de cromatografía líquida de baja presión. Las proteínas de interés eluyeron en las fracciones 21-25 y se sometieron a electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Promising results have been reported by Pan et al (23) which used an extender with SP concentration of 25% leading to effective preservation of the canine sperm motility and plasma membrane integrity in samples chilled at 4 °C. The inclusion of SP proteins with a molecular weight of 14 kDa and 16 kDa and isoelectric points between 5.0-5.5 in the preservation medium increased bull sperm viability (26). The use of seminal plasma proteins in the range of 12-20 kDa leads to improvement of biotechnological preservation of spermatozoa (27).…”
Section: Discussionmentioning
confidence: 99%
“…Promising results have been reported by Pan et al (23) which used an extender with SP concentration of 25% leading to effective preservation of the canine sperm motility and plasma membrane integrity in samples chilled at 4 °C. The inclusion of SP proteins with a molecular weight of 14 kDa and 16 kDa and isoelectric points between 5.0-5.5 in the preservation medium increased bull sperm viability (26). The use of seminal plasma proteins in the range of 12-20 kDa leads to improvement of biotechnological preservation of spermatozoa (27).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the excessive concentration of proteins competing for these sites may result in a lower amount of SP proteins bound to their target sites, resulting in lack of effect. Several authors have reported significant improvements in PM integrity of frozen‐thawed spermatozoa, washed or the unwashed, with SP or some SP proteins (Barrios, ; Leahy et al, ; Pérez‐Pé et al, ; Rueda A et al, ). However, unwashed sperm incubated with ‘raw or complete’ SP did not achieve PM integrity rates higher than 28% (Leahy et al, ; Rovegno et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of SP proteins to reverse the cryodamage has been documented on live gametes, usually when SP was added after swim‐up or density gradient selection techniques (Bernardini et al, ; Maxwell et al, ; Rovegno et al, ; Rueda et al, ). This suggests that SP proteins show beneficial effects when they are in contact with cell suspension depleted from their own SP and extender components.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that sperm quality can be improved or at least sustained by these specific proteins during cryopreservation [ 99 , 100 ]. Seminal plasma proteins having a low molecular weight (14–16 kDa) help maintain bovine sperm viability in a frozen medium [ 101 ]. Adding 1–1.5 mg of protein having M.W (14–16 kDa) elevated sperm viability by up to 20%.…”
Section: Addition Of Seminal Plasma Components and Other Supplementsmentioning
confidence: 99%